Glycine receptor mechanism elucidated by electron cryo-microscopy - Du, Juan; Lü, Wei; Wu, Shenping; Cheng, Yifan; Gouaux, Eric (Nature (London), 2015)
The strychnine-sensitive glycine receptor (GlyR) mediates inhibitory synaptic transmission in the spinal cord and brainstem and is linked to neurological disorders, including autism and hyperekplexia. Understanding of molecular mechanisms and pharmacology of glycine receptors has been hindered by a lack of high-resolution structures. Here we report electron cryo-microscopy structures of the zebrafish α1 GlyR with strychnine, glycine, or glycine and ivermectin (glycine/ivermectin). Strychnine arrests the receptor in an antagonist-bound closed ion channel state, glycine stabilizes the receptor in an agonist-bound open channel state, and the glycine/ivermectin complex adopts a potentially desensitized or partially open state. Relative to the glycine-bound state, strychnine expands the agonist-binding pocket via outward movement of the C loop, promotes rearrangement of the extracellular and transmembrane domain ‘wrist’ interface, and leads to rotation of the transmembrane domain towards the pore axis, occluding the ion conduction pathway. These structures illuminate the GlyR mechanism and define a rubric to interpret structures of Cys-loop receptors. A high-resolution electron cryo-microscopy structure of the zebrafish α1 glycine receptor bound to agonists or antagonists reveals the conformational changes that take place when the channel transitions from closed to open state. Glycine receptor mechanism Eric Gouaux and colleagues have determined the high-resolution electron cryo-microscopy structure of strychnine-sensitive glycine receptor (GlyR) from zebrafish, bound to agonists or antagonists to reveal the conformational changes that take place when the channel opens. GlyRs mediate neurotransmission throughout the spinal cord and brainstem and their dysfunction is linked to multiple neurological disorders, including autism and hyperekplexia. Also in this issue of Nature , Xin Huang et al . report the X-ray crystal structure of the human GlyR in the presence of the antagonist strychnine.